2010
DOI: 10.1116/1.3294707
|View full text |Cite
|
Sign up to set email alerts
|

Frequency modulation atomic force microscope observation of TiO2(110) surfaces in water

Abstract: Scanning tunneling microscopic analysis of Cu ( In , Ga ) Se 2 epitaxial layers J. Appl. Phys. 107, 034906 (2010); 10.1063/1.3304919 Ferroelectric relaxor behavior and microwave dielectric properties of Ba ( Zr 0.3 Ti 0.7 ) O 3 thin films grown by radio frequency magnetron sputtering

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…A UHV‐STM study of TiO 2 (110) before and after dipping the sample in water indicated that the surface might not be stable . This was also observed with atomic force microscope (AFM) measurements in liquid …”
Section: Introductionmentioning
confidence: 69%
“…A UHV‐STM study of TiO 2 (110) before and after dipping the sample in water indicated that the surface might not be stable . This was also observed with atomic force microscope (AFM) measurements in liquid …”
Section: Introductionmentioning
confidence: 69%
“…The high density of OH t groups (0.9 nm −2 ) was probably achieved by the dissociation of H 2 O molecules. The presence of a hydrogen-bonding network near the surface 22 suggests that a high density of H 2 O molecules coordinate to the O b and Ti 5c atoms, thereby forming the underlying structure for the hydration layer. Some of the OH t groups might associatively desorb, thus leaving O a atoms 18…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…This observation suggests retention of the (1 × 1) structure of the terraces upon its brief exposure to air. We also explored the imaging of the (1 × 1) surface immersed in water by noncontact atomic force microscopy (NC-AFM) . O b atom rows appeared, along with nanosized particles, hypothesized to be H 2 O clusters, aligned along the [001] direction.…”
Section: Introductionmentioning
confidence: 99%
“…FM-AFM imaging in liquids has been used for various samples, ranging from inorganic crystals , to biomolecules. , As mentioned above, atomic-scale AFM investigations of rutile and anatase TiO 2 in vacuum have already been reported. However, although AFM images with atomic-scale striped contrasts obtained at the rutile (110) surface in liquid have been reported, the contrasts within each stripe were not clear enough to allow their detailed comparison with an atomic surface model. To the best of our knowledge, there has been no report of atomic-scale AFM studies of TiO 2 surfaces in liquids, not only of brookite, but also of rutile and anatase.…”
Section: Introductionmentioning
confidence: 99%